Analysis of Significant Factors Influencing Employee Engagement in Startup Companies in Bandung (Journal of Innovation, Business and Entrepreneurship, 2020)
Indonesian startups has grown very rapidly in the last 5 years and currently the country ranks first in ASEAN and fifth globally in number of startups, and they are the hope for the Indonesian economy in the future. However, the fact shows that almost 90% of startups from various sectors from all over the world fail to develop their startups. There are several reasons why startups can fail to run their business, one of the important factors is a poor team. To avoid have a poor team, they need an employee engagement to increase the employee performance, individual participation, employee happiness and enthusiasm for work. However, startup have a lot of limitations such as capital, resources, and knowledge to increase their employee engagement. So, in this research, the author aims to help startup in Bandung to know what is the significant variable that influence employee engagement in startup company. The independent and dependent factors on this research are: Leadership, Organizational Culture, Rewards, and Employee Engagement.Keywords: : Leadership, Organizational Culture, Compensation, Employee Engagement